Traces of Hadhramaut Intellectualism and Its Influence on The Development of Da'wah of 21st Century in Indonesia - Fuadi, Moh Ashif; Mahbub, Moh; Ali, Nor Huda; Wahyudi, Muhammad; Trisnawati, Diana (Wawasan: Jurnal Ilmiah Agama dan Sosial Budaya, 2022)
Hadhramaut Yaman has a tradition of intellectualism that attract students in Indonesia. More and more students plan to deepen their religious knowledge at three pesantren (Islamic boarding schools) in Tarim, Hadhramaut, namely Darul Musthofa, Rubath Tarim, and al-Ahgaff University. This research discusses the historical study of Hadhramaut and traces of intellectualism between Hadhramaut Ulama (scholars) with Indonesian Ulama from the Kitab Kuning (yellow book) commonly studied in pesantren. In addition, it will analyse the role of Tarim Hadhramaut alumni in developing the da'wah movement in Indonesia. This research uses literature studies through a historical approach by collecting previous research through books, articles, online news, and library studies, field observations will also be conducted. This study shows that the genealogy trace between Walisongo and the Alawiyyin in Hadhramaut. In addition, the network of Hadhramaut Ulama with Nusantara has an intellectual impact, such as the book Safinatun najah by Sheikh Salim bin Sumair received appreciation by giving explanations and commentary by Nusantara Ulama. The Habib in Tarim still has a strong da'wah influence in Indonesia, especially after the first 30 students of Darul Musthofa became alumni and established ta'lim assembly or pesantren. Hadhramaut pesantren network is connected through santri (student) who studied at Darul Musthofa, Rubath Tarim, and al-Ahgaff University. The three institutions show an inclusive character suitable for application in Indonesian pesantren.